(untitled) (Revista Apotheke, 2025)
This article aims to revisit ideas from the philosopher John Dewey and suggest ways to reflect on the concept of experience for the Teaching of Visual Arts. The first section presents the influences of Dewey’s thought, recovering some approaches to experience and aesthetics in the history of philosophy to contextualize and highlight Dewey. The second section addresses mutual resonances of reflective thought and aesthetic experience. The third section disseminates the reflection of the report of a postgraduate class in visual arts, which had as its proposal to tear pages from a book and read them randomly. This proposition is described and substantiated as an aesthetic experience that enables interest, association and continuity in a teaching and learning process, or art as experience.